2014
DOI: 10.1093/jxb/eru007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and expression analysis of the grape (Vitis vinifera L.) WRKY gene family

Abstract: SummaryFifty-nine VvWRKY genes were identified. Phylogenetic tree and synteny analysis revealed the specific evolutionary relationship of these genes. Meanwhile, differential expression patterns indicated their possible roles in specific tissues and under different stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
250
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(271 citation statements)
references
References 65 publications
19
250
1
1
Order By: Relevance
“…The WRKY family genes confer multiple functions in plant developmental and physiological processes (Eulgem et al 2000;Miao and Zentgraf 2007;Zhou et al 2011;Guo et al 2014) and biotic and abiotic stress responses (Rushton et al 1996;Eulgem and Somssich 2007;Chen et al 2012). In cucumber, previous reports indicated that under normal growth conditions, there were 48 WRKY genes displaying differential expression in their transcript levels or in their expression patterns, and 23 WRKY genes exhibited expressional difference in response to at least one of three abiotic stresses including cold, drought and salinity) (Ling et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WRKY family genes confer multiple functions in plant developmental and physiological processes (Eulgem et al 2000;Miao and Zentgraf 2007;Zhou et al 2011;Guo et al 2014) and biotic and abiotic stress responses (Rushton et al 1996;Eulgem and Somssich 2007;Chen et al 2012). In cucumber, previous reports indicated that under normal growth conditions, there were 48 WRKY genes displaying differential expression in their transcript levels or in their expression patterns, and 23 WRKY genes exhibited expressional difference in response to at least one of three abiotic stresses including cold, drought and salinity) (Ling et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first WRKY gene, SPF1, was cloned from sweet potato (Ishiguro and Nakamura 1994), a large number of WRKY genes were identified and characterized from different plant species, such as tobacco (Yang et al 1999;Chen and Chen 2000), Arabidopsis (Eulgem et al 2000;Dong et al 2003), parsley (Cormack et al 2002), barley (Sun et al 2003), rice (Xie et al 2005;Ross et al 2007), coffee (Ramiro et al 2010), cucumber (Ling et al 2011), poplar (He et al 2012), soybean (Yin et al 2013), physic nut (Xiong et al 2013), brachypodium distachyon (Wen et al 2014), and grape (Guo et al 2014).…”
mentioning
confidence: 99%
“…The iPBS marker method has several advantages compared with other retrotransposon markers: iPBSs can discriminate among genotypes without prior sequence knowledge and are highly reproducible due to their primer length and the high stringency achieved by the annealing temperature (Guo et al, 2014b). Indeed, this marker system has been used successfully for several genetic diversity studies in plants, such as apricot (Baranek et al, 2012), Cicer species (Andeden et al, 2013), and Vitis vinifera (Guo et al, 2014a(Guo et al, , 2014b. Chen and Liu (2014) also reported that iPBS and start codon-targeted polymorphism markers are effective marker systems for discriminating genotypes in Myrica rubra.…”
Section: Introductionmentioning
confidence: 99%
“…Though WRKYGQK is highly conserved in most WRKY members, variant proteins such as WRKYGKK, WRKYGEK, WRKYEDK, WKKYGQK, CRKYGQK, WHQYGLK, WRKYGMK, WSKYGQK, WQKYGQK as well as WIKYGEN were identified in Solanum lycopersicum, Glycine max and Vitis vinifera (Huang et al 2012;BenckeMalato et al 2014;Guo et al 2014). WRKY motif sequence is followed by a C2H2-or C2HC-type zinc finger motif, with sequences of C-X 4-5 -C-X 22-23 -H-X-H and C-X 5-8 -C-X 25-28 -H-X 1-2 -C, however, there are some exceptions, e.g.…”
Section: Discussionmentioning
confidence: 99%